How media pluralism navigates ideological orientations: the case of Slovenia - Valič, Tamara Besednjak; Rončević, Borut; Tomšič, Matevž (Frontiers in Communication, 2023)
Introduction Media and its reporting shape public opinion, and doing this can obtain an indirect and significant influence on the course and results of the political process. In this context, media operates as an active element of the political process. Methods The authors use the Janis-Fadner coefficient of imbalance to analyze a total of 1434 media texts published in 10 different Slovenian media outlets. The texts were published between March and September 2020. Results The authors discover weak media plurality as the main characteristic of the Slovenian media space. The results show the majority of media reporting is strongly anti-right-wing-governmental and left-wing oriented with little pluralism. Most news coverage of web portals demonstrates a distinct ideological note, resulting in predominant expressions of centre-left and anti-center-right government views. Discussion Most analyzed media is significantly more unfavorable to the center-right government than the center-left opposition, taking a notable left-wing stance. Confirmed by previous conducted studies, the Slovenia's political left seems to have much stronger media support than its right-wing counterpart. For the purpose, would be important to observe whether demonstrated harsh anti-government and pro-opposition orientation changed following the establishment of a new left-wing government after April 2020 elections.